Silica nanoparticle toxicity: cellular mechanisms, neurotoxicological concerns, and environmental perspectives - Yuji Kamikubo; Hakushun Sakairi (Frontiers in Nanotechnology, 2025)
Engineered silica nanoparticles (SiNPs) are increasingly employed in various domains, including biomedicine and industry, owing to their tunable physicochemical properties. However, their extensive application has raised concerns about their potentially detrimental effects on human health and ecosystems. This mini-review summarizes current knowledge of the cellular mechanisms underlying SiNP cytotoxicity, with a focus on oxidative stress, NOD-like receptor protein 3 (NLRP3) inflammasome-mediated inflammation, lysosomal destabilization, mitochondrial dysfunction, genotoxicity, and autophagy modulation. We emphasize the critical influence of SiNP properties such as size, surface chemistry, shape, and synthesis method on these biological responses. Particular attention has been given to neurotoxicity, which is a growing concern owing to the potential of SiNPs to cross the blood-brain barrier. Additionally, we briefly address environmental considerations, recognizing the need to understand the fate and impact of SiNPs within ecosystems. Finally, we discuss mitigation strategies, including surface engineering and safer-by-design approaches, and delineate the key knowledge gaps and future research directions essential for the sustainable development and safe application of SiNP-based technologies in the context of both human health and environmental safety.